Factors Influencing Compliance Giving Measles Immunization Tobaby Toddler Age 9-18month - Maria Butu; Nur Al-faida; Gandhi Pratama (International Journal of Public Health, 2024)
Background:Measles is an infectious disease caused by the measles virus (morbillivirus). This disease is highly contagious and usually attacks children, although adults who have never been vaccinated or have never had measles are also at risk. Infants do not receive measles immunization at the Timeepa Health Center 50 children. If they do not receive complete and timely immunization, they will be more susceptible to various diseases that should be prevented by immunization, one of which is measles.Objective:To determine the effect of maternal knowledge, maternal occupation and maternal attitude on the provision of Measles Immunization to infants aged 9-18 months in the Timeepa Health Center Work Area. Method: Quantitative research type with a cross-sectional approach. The study population was 34 toddlers. The sampling technique used total sampling. Data analysis used the Statistical Program for Social Science (SPSS) version 16.0 application and used the chi-square test. Results: The test of the effect of maternal knowledge p-value 0.000 (<0.05), maternal occupation p-value 0.000 (<0.05), and maternal attitude p-value 0.015 (<0.05). Conclusion: There is an effect of maternal knowledge, maternal occupation and maternal attitude on the provision of measles immunization in the Timeepa Health Center Work Area. Suggestions:Conducting counseling on measles immunization and the importance of integrated health posts, types of activities at integrated health posts regarding measles immunization so that mothers go to integrated health posts more regularly every month and so that toddlers can receive measles immunization.